(untitled) (Third Sector Social Economic Review, 2017)
The purpose of this study is to influence the marketing activities of banks’ branch structures and the profitability of the bank. In the scope of the study, more literature was searched. It is an additional cost for the banks to go to the branch office, but the branching of banks is an advantage in terms of both acquiring customers and disributing loans and collecting deposits. Hence, The banks have spread their risks by brnaching. The banks are engaged in branding by actively conducting marketing activities and branching. Whether in Turkey or abroad, The banks have increased both their assets and reached a high level of profitability by branching.